The Implementation of National Curriculum 2013 and International Baccalaureate (Study at Sampoerna Academy Medan) - Mayolica Marsillam Toruan; Akrim Akrim; Indra Prasetia (Randwick International of Social Science Journal, 2022)
This study aims to determine the implementation of National Curriculum 2013 and the International Baccalaureate curriculum and to compare student learning outcomes, especially in the field of Indonesian language studies at Sampoerna Academy Medan. The results shows that there are differences in learning outcomes in the field of Indonesian language studies using National Curriculum 2013 and the International Baccalaureate. The difference in the level of ability of students in the field of Indonesian language studies is indicated by the average learning outcomes of Indonesian language studies with National Curriculum 2013 which is lower than the International Baccalaureate curriculum. The findings of this study indicate that the use of both National Curriculum 2013and the International Baccalaureate has an impact on student learning outcomes at Sampoerna Academy Medan. This difference is due to differences in assessment standards, learning activities, communication both oral and written as well as the values ​​of cultural and character development of each curriculum applied in schools.